RAT (Rattus rattus diardii L.) Repellent Made of Soursop (Annona muricata L.) Leaves Extract - Meida Dewanti; Fatona Wahyu Pandi Hastuti; Titis Dhian Novita; Rizqi Triananda; Arif Jumari (Program studi Teknik Kimia UNS, 2018)
House rat (Rattus rattus) is a rodent that can damage any objects at home and leave manure there by resulting in bad odor and rat also becomes a host of some disease vectors. The use of plant repellent is one alternative control utilizing rat’s olfactory sense. The Soursop (Annona muricata L) is a plant with very stinking aroma and very disliked by rat, thereby can be used as plant repellent. The aim of the research was to extract the soursop leaves and to use its extract as the active material of rat repellent. The methods employed in preparing of rat repellent from soursop leaves were grinding and maceration extraction using two different solvent, water and ethanol 96 wt%. The extract was then examined as an active material of rat repellent. The examination was conducted by adding the soursop extract to the rat food. The resultsshowed that the loss of rat food with repellent made of grinded soursop leaves was 1%, while with repellent made of combined grinded soursop leaves and ethanol was 2.48%. The loss of rat food with repellent made of water solvent soursop exstract leaves was 64.5%, and that using repellent made of ethanolsolvent soursop was 16.67%. So, the utilization of soursop leaves as rat repellent was expected to reduce rat population in the people’s houses.